Improving skills and productivity of disadvantaged youth - Freedman, David H. (ILO GenevaCH, 2008)
Focuses on targeted interventions for those youth whose circumstances place them at particular risk of not being employed. Examines interventions that have been undertaken and comments on what more needs to be done.